SUPPLY CHAIN PRACTICES OF SMALL AND MEDIUM ENTERPRISES AS A MAXIMIZED EFFORT OF HUMAN RESOURCE PERFORMANCE STRATEGY IN TOURISM SECTOR - Hermawati, Adya; Suhermin, Suhermin; Suci, RahayuPuji; Karyanto, Budi (International Journal of Supply Chain Management, 2020)
Abstract?This research aims to map the internal and external condition of SMEs in supply chain performance of tourism sector and determines the effective strategy to increase the human resource performance for each region. This research was conducted in East Java that has the most SMEs in Indonesia. Sampling was done in two stages, namely (1) selecting districts and (2) selecting MSMEs. The results of the sampling process were taken by 20 MSMEs in each district selected as a sample. SWOT was used as an analysis tool in this study. Malang Regency has the most unique conditions, namely strong internal conditions, but has considerable challenges. The models presented in this paper give an informed insight and understanding of the dynamic changes that can transform SMEs within their supply chain relationships.